What Makes International Students Choose Malaysian Higher Learning Institutions? A Meta-Analysis 2007-2019 - K. Haniya, Osama; Said, Hamdan; Mohamad Nor, Faizah (International Journal of Psychosocial Rehabilitation, 2020)
The selection of a particular higher education institution is an important matter that may shape not just the life and accomplishment of students’ careers but also their families. The aim of the current study is to investigate the factors that influence the students’ choice of Malaysian higher education institutions through reviewing previous literature. A meta-analysis was conducted on several previous studies to figure out the factors that influence students in making a decision on their choice. Previous studies were retrieved from ERIC, ScienceDirect, ResearchGate, SpringerLink, and EBSCO with a focus on the Malaysian context. The results showed that students give high consideration to facilities, learning environment, education quality, reputations, and location when making a choice to study at higher education institutions. The results of this study may provide valuable information for Malaysian higher education institutions on the criteria they are required to focus on to attract international students to study in their institutions.